Health Perception and Behaviors in Adults With Bronchiectasis - Guan, Wei-Jie; Yuan, Jing-Jing; Li, Hui-Min; Huang, Yan; Chen, Chun-Lan; Gao, Yong-Hua; Chen, Rong-Chang; Zhong, Nan-Shan (Respiratory care, 2019)
Bronchiectasis is a chronic debilitating suppurative disease that significantly impacts quality of life. Clinical outcomes like exacerbations, are usually physician centered; however, the patients' experience, health-related behaviors, and expectations have frequently been neglected. In addition, patients' health perceptions may be influenced by their culture. To determine the health perception and behavior in adults with bronchiectasis. We performed semi-directive interviews, which were audiotaped, with 60 adults with bronchiectasis between April 2016 and December 2016. Our interview focused on issues related to symptom perception, access to health-care resources and patient-physician communication, medication adherence, outcomes and expectations, quality of life, and social relationships. The subjects with bronchiectasis developed varying patterns of symptom perception (ranging from highly distressing to barely disturbing) and had conflicting opinions on whether and when they should seek health-care services (ranging from active consultations to being totally passive or resistant to seek health care). We observed certain discrepancies between symptom perception and health-related behaviors. Overall, medication adherence was suboptimal, but the subjects were willing to participate in clinical trials and receive complementary alternative medications despite concerns regarding adverse effects of prolonged treatment. There were concerns about the adverse effects of bronchiectasis on fertility and infectiousness to others, although most subjects disregarded these issues. The diverse symptom perception and health-related behaviors highlighted the need for evaluation and intervention in bronchiectasis. These findings will provide rationales for refining future health care through comprehensive (particularly psychological) interventions worldwide.